Case report of two brothers with a novel homozygous mutation in ALOX12B leads to autosomal recessive congenital ichthyosis: Which type and which subtype? Two siblings with a novel homozygous mutation in ALOX12B - Evren Gumus (Dermatologica Sinica, 2019)
Ichthyosis is a heterogeneous group of rare genetic skin disorders characterized by furfuraceous and dry skin. The classification of ichthyosis has always been a challenging process as genodermatoses. Here, we report a novel homozygous mutation in ALOX12B in two siblings with autosomal recessive congenital ichthyosis. We aimed to evaluate two brothers' genotype-phenotype association in the light of the last nomenclature information.